Optimal Selection of COVID-19 Serological Testing Kits - Ashankyty, Ibraheem (Journal of Oral Diagnosis, 2020)
Immunization is the ultimate objective to ensure safe return, for schools and jobs to be open. Fortunately, the government of Saudi Arabia had announced that Clinical trials for SARS-CoV-2 will start in August 2020. There is need to evaluate immune response among vaccinated individuals and recovered patients. The market is full of different commercial tests promoted for the health care providers. An accurate selection of tests is crucial specially that are approved by international authorities the FDA-CDC. By August 2020, forty-seven serology tests were authorized by the FDA-CDC under the -EAU emergency. The accuracy and reliability of the serological tests is reflected by the sensitivity and specificity of the test. However, serological testing has an inherent problem of false positive and false negative that are associated with tests. Therefore, the sensitivity and specificity values are not enough indicators for the interpretation of the results specially in variation of the prevalence rate. The positive predictive value (PPV) was calculated from sensitivity and specificity of 47 tests at different prevalence rates to show its effect on the interpretation of results at different populations. In conclusion, it is time to use serological testing for the public to return to normal life. Selecting the proper serological kit depends heavily on the specificity, more than the sensitivity, of the test and the prevalence of the disease among the group tested. In lower prevalence population use two kits to increase the PPV and reliability of the results.